MATRIK-IE : STRATEGI PEMERINTAH KOTA DALAM MENGOPTIMALKAN POTENSI PENANAMAN MODAL - Sulasti Sulasti; Udin Rinaldi (STIE 'INDONESIA' Pontianak, 2022)
The research objective is to determine the direction of the government's strategy in optimizing investment potential. This research uses descriptive analysis by collecting primary and secondary data about the achievement of the results in the form of everything that is owned (inventory) by the city government, case study on Singkawang city of Kalbar. Data collection tools through questionnaires (on informants), observation and observation at the location of the object of research. The analysis model used uses two stages, namely the first stage of data collection, which includes the External Factor Evaluation Matrix and the Internal Factor Evaluation Matrix. Second, the analysis stage using the Internal External matrix. The results of the IFE and EFE analysis research show that the ability or potential for investment in the City of Singkawang is classified as strong in utilizing existing strengths in overcoming weaknesses and overcoming threats. Based on the IE matrix, the chosen strategy is Grow and Build, so the suitable strategy to use in optimizing investment potential is an intensive strategy or an integration strategyTujuan penelitian adalah untuk menentukan arah strategi pemerintah dalam mengoptimalkan potensi penanaman modal. Penelitian menggunakan analisis deskriptif dengan mengumpulkan data primer maupun sekunder tentang pencapaian hasil berupa semua yang dimiliki (inventarisasi) oleh pemerintah kota, studi kasus kota Singkawang Kalbar. Alat pengumpulan data melalui angket (pada informan), observasi maupun pengamatan pada lokasi objek penelitian. Model analisis yang dipakai menggunakan dua tahap, yaitu pertama tahap pengumpulan data, meliputi matrik Evaluasi Faktor Eksternal dan matrik Evaluasi Faktor Internal. Kedua, tahap analisis dengan matrik Internal Ekternal. Hasil penelitian analisis IFE dan EFE menunjukan bahwa kemampuan atau potensi penanaman modal Kota Singkawang tergolong kuat dalam memanfaatkan kekuatan yang ada dalam mengatasi kelemahan dan mengatasi ancaman. Berdasarkan matrik IE strategi terpilih adalah Grow and Build sehingga strategi yang cocok digunakan dalam mengoptimalkan potensi penanaman modal adalah strategi intensif atau strategi integrasi